Functional connectome integration observed after antispastic epidural cervical spinal cord stimulation in a patient with TBI-induced disorder of consciousness: a case report - Mayorova, Larisa Alexeevna; Bondar, Ekaterina Leonidovna; Radutnaya, Margarita Leonidovna; Yakovlev, Alexey Alexandrovich (Frontiers in Human Neuroscience, 2025)
We report the case of a patient with disease of consciousness who underwent 6 days of antispastic spinal cord stimulation followed by consolidation of a functional connectome as measured by resting state fMRI (rs-fMRI). The test spinal cord stimulation (SCS) system (with electrodes placed epidurally at the C3-C5 level) was used to evaluate its potential to relieve muscle contracture as the primary clinical target. Neurological and rs-fMRI examinations were performed before and after surgical placement of the spinal cord stimulation system. For neurological assessment of spasticity we used the Ashworth scale. To analyze fMRI, we used the extraction of functional connectivity coefficients and the construction of a connectivity matrixes. To construct a normative matrix of functional connectivity, 10 healthy volunteers of appropriate age were recruited as a control group. Analysis of rs-fMRI data showed that after a short course of epidural cervical spinal cord stimulation, the patient’s functional connectivity matrix similarity with the control group increased, which was manifested in the growth of ROI-to-ROI and inter-network functional connectivity coefficients. This finding may indicate the complexity of the neuromodulatory effect of spinal cord stimulation and its consolidating effect on the functional connectome of the brain, including brain regions associated with the function of maintaining arousal and awareness, even when the clinical effect is not perceptibly pronounced. We supposed to conduct the spinal cord therapy for this patient in a permanent way not only to relieve spasticity but also to support consciousness. We assume that functional connectome assessment in such clinical cases may help to give additional arguments in SCS-therapy prescription in patients with disorders of consciousness as well as to understand in the future the pathophysiological mechanism of the effect of this procedure.